Performance improvement of cascaded H-bridge multilevel inverters with modified modulation scheme - Lee, Eui Jae; Lee, Kyo Beum (Journal of Power Electronics, 2021)
This study proposes a modified modulation scheme based on the phase-shifted pulse-width modulation (PS-PWM) method to improve the output performance and reduce the switching loss in cascaded H-bridge multilevel inverters. The PS-PWM method is one of the most popular modulation schemes. However, it generates significant switching loss, which can lead to the failure of power semiconductor switches. Various studies have proposed modulation schemes to reduce switching loss. The clamped discontinuous PWM (DPWM) method achieves the best switching loss reduction performance in comparison with other modulation schemes. However, the clamped DPWM method has low output characteristics, such as total harmonic distortion. The proposed modulation scheme achieves the same switching loss reduction and improved output performance by modifying the dwell time order. The proposed evenly clamped DPWM method was compared with the conventional clamped DPWM method through simulations and experiments.
Keywords: Cascaded h-bridge multilevel inverters; Discontinuous PWM; Modulation schemes; Output characteristics; Output performance; Phase shifted pulse; Power semiconductor switches; Total harmonic distortion (THD); Cascaded H-bridge multilevel inverter; Discontinuous PWM; Phase-shifted PWM; Switching loss reduction; Total harmonic distortion improvement